Tingkat Aksesibilitas Halte BRT di Kecamatan Banyumanik - Annisa Bayanti Nusantara; Jawoto Sih Setyono (Jurusan Perencanaan Wilayah dan Kota, 2019)
Banyumanik District is a new growth center that tends to develop towards the suburbs. The development of a new growth center was followed by an increasing population in Banyumanik District and is currently dominated by the productive age population. The more developed Banyumanik District, the more needs that must be met, such as transportation. It is seen from the number of productive age population in Banyumanik District while the activity center is in the center of Semarang City. Trans Semarang is a public transportation that is provided to fulfill the needs of the citizen for transportation, but until now it still has a small number of enthusiasts, as seen from the average load factor rate of 45.72%. Accessibility to shelters is very important in the operation of Trans Semarang because Trans Semarang is a closed public transportation system. The purpose of this research is to find out the conditions of accessibility and the level of accessibility of shelter according to perspective of productive age population in Banyumanik District. The analytical tools used are scoring and descriptive statistics. The results of the analysis showed that the accessibility level of shelters in Banyumanik District is divided into 3 levels, namely Level V, Level VI, and Level VII but overall Banyumanik District falls into Level VI with a score of 92.14. This means that the accessibility of shelters is moderate but tends to be bad based on each condition forming the accessibility factor for the shelter.